"Epilepsy is pathognomonic of witchcraft": parental perspectives on childhood epilepsy and their treatment choices in South West Uganda. (24th May 2012) - Bodey, C
Abstract : Childhood epilepsy is a common, socially stigmatising and largely treatable disease. Despite this there remains a large treatment gap between the number of children with epilepsy and the number receiving appropriate anti-epileptic drug (AED) treatment. To understand reasons for the treatment gap, treatment methods and beliefs of carers were prospectively analysed for 18 children with epilepsy attending the paediatric neurology clinic at a government hospital in Uganda. The majority of carers (61%) believed that their child's seizures had a supernatural explanation. Of these, 40% believed that their child had been bewitched or possessed by evil spirits and 50% believed that their child's seizures were caused by "Ebihungu" (meaning "birds"). 83.3% of the children with epilepsy had used complementary therapists before attending a Western medical health facility. Of the respondents using complementary therapists, 73.3% used traditional healers alone, 6.7% used spiritual healers alone, and 20% had been treated by both. Traditional healers used herbal remedies, charms, rattles or scarification marks. The cost of visiting hospital was considerable, both in transport costs and time away from farming. Traditional healers incurred great cost in the purchasing of herbal remedies. The average duration of time before starting appropriate AEDs was less than one month for children who received no complementary therapy, and 22 months for children receiving treatment from traditional healers. The influence of the family's social network on treatment seeking behaviours was considerable. 46% patients continued to use traditional medicine or spiritual healing whilst taking AEDs, suggesting many of the caregivers perceived some continuing benefit from these alternative treatments. The popularity of alternative practitioners in the treatment of epilepsy and their continued use when taking AEDs underlines the perceived usefulness of the treatments they offer. Programmes to decrease the treatment gap in childhood epilepsy would need to include close collaboration of Western medical practitioners with traditional healers, who could help identify and refer children with epilepsy, whilst continuing to play a supportive role in the community in a culturally sensitive way. This collaboration is important as neither Western medicine nor complementary therapists can satisfactorily manage the needs of the patient and their family alone.